The oldest gold mining law in Silesia - Szymański, Jarosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
In Silesia, the beginnings of gold mining date back to the turn of the 12th and 13th centuries. The first attempt to legally regulate gold mining was the short mining act found in the municipal book of Lwówek Śląski, dated to the first half of the 13th century. In 1342 Dukes of Legnica, Wenceslaus I and Louis I, issued such a law for Złotoryja. These legal acts, particularly the one of Złotoryja, are the most important regulations regarding the medieval gold mining in Silesia.They relied on the local traditions and experiences; therefore, they feature no borrowings from the Czech or Saxon mining legislation. This can be explained with the “ancient” tradition of gold mining in the area of Złotoryja and Legnica, which allowed for development and establishment of native legal solutions. By ordering to write down such local rules, the dukes confirmed the individual mining traditions of their duchies, which was favourable from their perspective because the tradition pointed to exclusive right of the duke, without accounting for mining local governing bodies. This article presents the oldest legislation regulating gold mining in Silesia. It provides the Polish translation of the laws of Lwówek and Złotoryja, and discusses major rules in comparison to analogical legislation functioning in Bohemia.
Keywords: gold mining; mining law; Silesia; Duchy of Legnica; Louis I; Wenceslaus I